Determinants of Corporal Punishment and Severe Physical Punishment in Egypt: A Mixed-Methods Analysis for Child Protection Policy - Nassef, Marwa Moustafa (AUC Knowledge Fountain, 2026)
Corporal punishment (CP) and severe physical punishment (SPP) remain a major public health, child rights, and child protection policy concern. In Egypt, despite legislative reforms, survey-weighted analysis of the 2021 Egypt Family Health Survey (EFHS) 2021 (CAPMAS, 2022) reveals prevalence rates of 60.5% for CP and 27.4% for SPP among children aged 1–14 (author’s calculations using EFHS-2021, n=7623), yet evidence distinguishing the determinants of routine corporal punishment from escalation to severe physical punishment remains limited in low- and middle-income contexts. Guided by Bronfenbrenner’s ecological framework, this mixed-methods study identifies key drivers of CP and its escalation to SPP among Egyptian households with children aged 1–14. Quantitatively, two survey-weighted logistic regression models (n=6,685) show that child gender (boys), maternal beliefs approving CP, household crowding, barriers to maternal healthcare, and exposure to intimate partner and domestic violence significantly increase the odds of both CP and SPP. Qualitatively, in-depth interviews with mothers contextualize these patterns, revealing how emotional dysregulation, intergenerational exposure to violence, perceived societal threats, and an overburdened education system interact to normalize harsh discipline. Qualitative findings suggest that parents often resort to corporal punishment, not always out of conviction, but in response to limited access to non-violent alternatives and cumulative structural stressors. The study concludes by outlining the implications for child protection policy.